In Vitro Activities of DA-7157 and DA-7218 against Mycobacterium tuberculosis and Nocardia brasiliensis - Vera-Cabrera, Lucio (American Society for Microbiology, 2006)
The in vitro activities of DA-7157, a novel oxazolidinone, against clinical isolates of Nocardia brasiliensis and Mycobacterium tuberculosis were determined. Equal MIC(50)s and MIC(90)s (0.25 and 0.5 μg/ml, respectively) were found for susceptible and multidrug-resistant isolates of M. tuberculosis. The N. brasiliensis isolates showed an MIC(90) of 1 μg/ml and an MIC(50) of 1 μg/ml. The DA-7157 prodrug, DA-7218, exhibited similar MICs for M. tuberculosis but fivefold-higher MICs for N. brasiliensis.